The Battle of Five Days and Five Nights in Palembang in Defending Indonesia's Independence in 1945 - ., Sukardi; ., Gunahardi; ., Djono (KnE Social Sciences, 2024)
The incident of the five-days and five-nights war, that took place in Palembang on 1-5 January 1947, was a struggle for the people of Palembang, South Sumatra, to maintain Indonesian independence from the Dutch who wanted to occupy the Palembang region. This has received criticism in history related to the struggle of the people of Palembang. They had put efforts not only to maintain the independence. but also to maintain the source power nature. The objective of this study is to analyze the events of five days and five nights of struggle to maintain Indonesian independence in 1945. This study uses the method history with technique data collection using heuristics, data verification, and techniques of data analysis using interpretation history and past historiography. Research results explain that the events of five days and five nights in Palembang which occurred in 1947 were battle among the people of Palembang, South Sumatra, who faced Dutch soldiers in the fierce war in the center of the city of Palembang. Point battles included fort Kuto Besak, Caritas, and the region’s old airport or area Tulung betutu. This paper is relevant to the struggle of people for Indonesia’s independence, which reflects a sense of kinship and comradeship in liberating. Keywords: struggle, independence, Palembang.